La baja de la tasa de ganancia y la crisis del capitalismo - Burgueño, Fausto (1979)
One of the fundamental problems of political economy is that concerning the law of the falling rate of profit, which in Marx's texts is considered the most important of political economy and which, as he himself reminds us, despite its simplicity, had not been fully understood. Hence, he maintained a constant discussion with classical political economy, particularly with Smith and Ricardo, on this central aspect of the accumulation of capital in which, although all the classics, and above all Ricardo, emphasize the natural tendency of profit to decrease, they fail to understand the real causes of this tendency or to explain the assumptions on which it is based.